Reward sensitivity predicts dopaminergic response in spatial neglect. (January 2020) - Li, Korina; Bentley, Paul; Nair, Ajoy; Halse, Omid; Barker, Gareth; Russell, Charlotte; Soto, David; Malhotra, Paresh A.
Abstract: It has recently been revealed that spatial neglect can be modulated by motivational factors including anticipated monetary reward. A number of dopaminergic agents have been evaluated as treatments for neglect, but the results have been mixed, with no clear anatomical or cognitive predictors of dopaminergic responsiveness. Given that the effects of incentive motivation are mediated by dopaminergic pathways that are variably damaged in stroke, we tested the hypothesis that the modulatory influences of reward and dopaminergic drugs on neglect are themselves related. We employed a single-dose, double-blind, crossover design to compare the effects of Co-careldopa and placebo on a modified visual cancellation task in patients with neglect secondary to right hemisphere stroke. Whilst confirming that reward improved visual search in this group, we showed that dopaminergic stimulation only enhances visual search in the absence of reward. When patients were divided into REWARD-RESPONDERs and REWARD-NON-RESPONDERs, we found an interaction, such that only REWARD-NON-RESPONDERs showed a positive response to reward after receiving Co-careldopa, whereas REWARD-RESPONDERs were not influenced by drug. At a neuroanatomical level, responsiveness to incentive motivation was most associated with intact dorsal striatum. These findings suggest that dopaminergic modulation of neglect follows an 'inverted U' function, is dependent on integrity of the reward system, and can be measured as a behavioural response to anticipated reward.